Magnetic properties of irradiated quasi 2D type II superconductors: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Braverman, G. M.; Gredeskul, S. A.; Avishai, Y. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
Persistent scaling behavior of magnetization in layered high Tc superconductors with short-range columnar defects is explained within the Ginzburg-Landau theory. In the weak field region, the scaling function differs from that of a clean sample and the critical temperature is renormalized due to defects. In the strong field region, defects are effectively suppressed and the scaling function, as well as the critical temperature are the same as in a clean superconductor. This picture is consistent with recent experimental results.